Technology-Supported Parent–Teacher Communication for Strengthening Learning Partnerships: A Systematic Literature Review - Agustina, Dhian Nur; Utari, Rahmania (Tekno - Pedagogi : Jurnal Teknologi Pendidikan, 2026)
Effective parent–teacher communication is a fundamental component of technology-supported learning partnerships that promote student learning and strengthen collaboration between schools and families. However, the rapid expansion of digital communication technologies has transformed interaction patterns while introducing new challenges related to equity, accessibility, and parental capacity. This systematic literature review synthesizes empirical evidence on technology-supported parent–teacher communication in elementary education, with particular attention to communication approaches and parental background factors influencing their implementation. Following the PRISMA framework, a systematic search was conducted in the Scopus database, covering publications from 2020 to 2025. Sixteen peer-reviewed empirical studies that met the inclusion criteria were analyzed through thematic synthesis. The findings reveal four complementary communication approaches: technology-enhanced communication, telephone-based communication, face-to-face interaction, and school-based meetings and collaborative activities. Among these, digital technologies—including email, instant messaging applications, learning management systems, and video conferencing platforms—emerged as the dominant infrastructure for sustaining continuous communication and supporting collaborative learning partnerships. Nevertheless, the effectiveness of these technologies is strongly influenced by parental socioeconomic status, employment conditions, educational attainment, cultural and linguistic background, and digital literacy, all of which shape access to, engagement with, and responsiveness toward school communication. These findings suggest that technology should be implemented as an inclusive pedagogical enabler rather than merely a communication medium. Schools are therefore encouraged to adopt flexible, multimodal, and context-responsive communication strategies that accommodate diverse family characteristics while fostering sustainable partnerships within technology-enhanced learning ecosystems.